MENGHADAPI DILEMA ETIKA PROFESI GURU DI ERA DIGITAL - Lutfiyah, Rifqi; Nur Khasanah; Zulva Alwan Faozi; Muhammad Hafizh Fikri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The digital transformation has significantly reshaped the educational landscape while simultaneously giving rise to increasingly complex ethical challenges for teachers as professionals. This study aims to identify various forms of ethical dilemmas faced by teachers in the digital era and to examine appropriate strategies to address them. The research employs a qualitative descriptive approach through a literature review and analysis of digital education practices. The research procedures include defining the problem focus, collecting data from scholarly sources, conducting thematic analysis, and drawing conclusions. The findings reveal that ethical dilemmas are associated with inappropriate use of social media, violations of student privacy, blurred professional boundaries between teachers and students, and the demands of integrating digital learning technologies. Moreover, limited digital literacy skills and the absence of robust ethical guidelines further intensify these challenges. Therefore, this study concludes that strengthening professional ethical codes, enhancing digital literacy competencies, and providing institutional policy support are essential to assist teachers in navigating ethical dilemmas responsibly and professionally in the digital era.